2015
DOI: 10.18805/lr.v0iof.6853
|View full text |Cite
|
Sign up to set email alerts
|

Somaclonal variation for genetic improvement in grasspea (<italic>Lathyrus sativus</italic> L.)

Abstract: Somaclonal variation was revealed among regenerants in four genotypes (Nirmal, P24, Nayagarh local and Dhenkanal local) of grasspea (<italic>Lathyrus sativus</italic> L.) following long term in vitro culture of internode explants. Most of the somaclones which survived till maturity had revealed chromosomal abnormalities and variation in one or more morphological and/or agronomic traits. Some of the variant phenotypes especially those relating to developmental variations were not inherited to R2 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…The result indicated that under the moisture stress condition maximum hundred seed weight was observed from the somaclonal plants whereas under non-stress condition maximum hundred seed weight was obtain from the parental genotype. This was in agreement with the result of Tripathy et al [26] in grass pea who reported better performance of the somaclones for hundred seed weight. On the contrary, Bouiamrine et al [19] reported hundred seed weight of somaclonal plants did not show better performance compared to the parental genotypes in durum wheat.…”
Section: Evaluation Of Somaclones (R1 Generation) and Their Respectivsupporting
confidence: 93%
See 1 more Smart Citation
“…The result indicated that under the moisture stress condition maximum hundred seed weight was observed from the somaclonal plants whereas under non-stress condition maximum hundred seed weight was obtain from the parental genotype. This was in agreement with the result of Tripathy et al [26] in grass pea who reported better performance of the somaclones for hundred seed weight. On the contrary, Bouiamrine et al [19] reported hundred seed weight of somaclonal plants did not show better performance compared to the parental genotypes in durum wheat.…”
Section: Evaluation Of Somaclones (R1 Generation) and Their Respectivsupporting
confidence: 93%
“…The differences among the means of the somaclones and their respective parental genotypes for the studied parameters were highly significant (P ≤ 0.01) for both experimental conditions (Table 2). In line with the present results, significant differences through the in vitro regenerated plants and the donor parents have been reported previously in many crops [19,[24][25][26].…”
Section: Evaluation Of Somaclones (R1 Generation) and Their Respectivsupporting
confidence: 91%
“…Taxonomic relationship studies have shown that only two species, L. amphicarpos and L. cicera, produce viable hybrids when crossed with L. sativus (Yunus and Jackson 1991). Yet, to overcome strong reproductive barriers among different species, biotechnological tools, including tissue culture, somaclonal variation, and protoplast fusion techniques may also be utilized (Ochatt et al 2001;Piwowarczyk and Pindel 2015;Tripathy et al 2016).…”
Section: Variety Amelioration Researchmentioning
confidence: 99%
“…Among the different explants of grass pea, the epicotyl was reported to be the most responsive with high shoot proliferation frequency. Development of somaclones in L. sativus is limited (Santha and Mehta, 2001 ; Tripathy et al, 2016 ; Barpete et al, 2020a ), but in India, such efforts have developed somaclones derived low-ODAP variety (Ratan) (Mehta et al, 1994 ; Santha and Mehta, 2001 ). Tripathy et al ( 2016 ) have also developed a series of somaclones for morphological, cytological (genetic) variation, and biochemical levels in four grass pea (Nirmal, P 24, Nayagarh local, and Dhenkanal local) genotypes.…”
Section: Breeding Approaches For Cultivar Developmentmentioning
confidence: 99%
“…A high-yielding and low ODAP somaclone (cv. NGOG 5) was developed that may be the potential candidate for future grass pea breeding programs (Tripathy et al, 2016 ). Ochatt et al ( 2002 ) and Barpete et al ( 2020a ) developed an in vitro system for shortening the generation cycles and hastening the breeding process coupled with the in vitro stages that provide up to 4–5 cycles per year of grass pea.…”
Section: Breeding Approaches For Cultivar Developmentmentioning
confidence: 99%